Impact assessment of an active transport intervention via systems analytics (2024)
The assessment of urban transport interventions is complex, multi-faceted, and context-dependent. This study proposes a multi-methodology approach called systems analytics to evaluate the potential impact of the implementation of temporary bike paths during the COVID-19 pandemic on Bogotá’s bicycle complex system. The proposed methodology applies systems theory to identify the complexity, barriers, and facilitators of the system and uses statistical and simulation methods to assess the potential impact of temporary bike paths on the safety and quality of life of bicycle users in Bogotá during the COVID-19 pandemic. The results of the case study indicate that the temporary bike paths could have been a factor that helped reduce bicycle collision rates (by 56%), increased the use of street segments classified with low levels of traffic stress (by 6.22%), and prevented premature deaths (145 per year). The proposed methodology is helpful for policymakers who aim to design active transport interventions in support of a sustainable and healthy environment.